Indocyanine green fluorescence lymphography during gastrectomy after initial endoscopic submucosal dissection for early gastric cancer. Issue 6 (7th February 2020) - Roh, C K; Choi, S; Seo, W J; Cho, M; Son, T; Kim, H-I; Hyung, W J
Abstract: Background: Indocyanine green (ICG) fluorescence lymphography can be used to visualize the lymphatic drainage of gastric cancer. Few studies have been performed to identify lymphatic drainage patterns after endoscopic submucosal dissection (ESD). ESD results in changes to lymphatics owing to fibrosis of the submucosal layer. This study aimed to evaluate the efficacy of ICG fluorescence lymphography for visualization of lymphatic drainage after ESD, and to assess its clinical application in additional gastrectomy after ESD for early gastric cancer. Methods: All patients who underwent gastrectomy after ESD between 2014 and 2017 in a single centre were reviewed. ICG was injected endoscopically into the submucosal layer around the ESD scar the day before surgery. At the time of surgery, lymph nodes (LNs) were visualized and lymphadenectomy was performed with near-infrared imaging. Ex vivo, all LNs were examined for the presence of fluorescence. Number of LNs resected and number of tumour-positive LNs were compared between patients who underwent near-infrared imaging and those who had conventional lymphadenectomy without intraoperative imaging. Results: Some 290 patients underwent gastrectomy after ESD, 98 with fluorescence lymphography-guided lymphadenectomy and 192 with conventional lymphadenectomy. Fluorescence lymphography visualized lymphatic drainage in all patients, without complications related to ICG injection or near-infrared imaging. Fluorescence lymphography visualized all stations containing metastatic LNs. The sensitivity for detecting LN metastasis in fluorescent stations was 100 per cent (9 of 9 stations), and the negative predictive value was 100 per cent (209 of 209). One patient with LN metastasis had one non-fluorescent metastatic LN within a fluorescent station. Conclusion: Fluorescence lymphography successfully visualized all draining LNs after ESD, with high sensitivity and negative predictive value for detecting LN metastasis. Fluorescence lymphography-guided lymphadenectomy could be an alternative to systematic lymphadenectomy during additional surgery after ESD. Graphical Abstract: Indocyanine green fluorescence lymphography clearly visualized draining lymphatics during additional surgery after removal of the primary lesion by endoscopic submucosal dissection. Moreover, it visualized all stations containing lymph node metastasis. Fluorescence lymphography-guided lymphadenectomy may be a potential alternative to systematic lymphadenectomy for additional surgery. Bright future?